2008
DOI: 10.1016/j.matchemphys.2008.03.022
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature oxygen non-stoichiometry, conductivity and structure in strontium-rich nickelates La2−xSrxNiO4−δ (x=1 and 1.4)

Abstract: Oxygen nonstoichiometry, electrical conductivity and thermal expansion of

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…All single-phase oxides were indexed in the tetragonal space group I4/mmm. These results are in a good agreement with those reported earlier [1,[23][24][25][26][27][28][29]. However, it should be noted that Millburn et al [29] prepared the single-phase LaSrNi 0.5 Mn 0.5 O 4 only under dried deoxygenated argon flow at 1200-1300°C, but not in air.…”
Section: Resultssupporting
confidence: 91%
“…All single-phase oxides were indexed in the tetragonal space group I4/mmm. These results are in a good agreement with those reported earlier [1,[23][24][25][26][27][28][29]. However, it should be noted that Millburn et al [29] prepared the single-phase LaSrNi 0.5 Mn 0.5 O 4 only under dried deoxygenated argon flow at 1200-1300°C, but not in air.…”
Section: Resultssupporting
confidence: 91%
“…Huang et al [135] also observed a structural transition (i.e., orthorhombic-tetragonal transition) of LNO 214 between RT and 150 °C, above which no phase transition occurred. LSNO 214 is expected to have a different thermal expansion behavior owing to a change in δ from adding Sr content [42,136,137,138]. Although the tetragonal structure of LSNO 214 (Sr = 0.2 and 0.4) was retained over the temperature range between 600 and 900 °C, thermal expansion coefficients increased with increasing Sr content [138].…”
Section: Control Of Oxygen Stability In Rp Oxidesmentioning
confidence: 99%
“…Although the tetragonal structure of LSNO 214 (Sr = 0.2 and 0.4) was retained over the temperature range between 600 and 900 °C, thermal expansion coefficients increased with increasing Sr content [138]. Makhnach et al [136] reported significantly different high-temperature behavior of LSNO 214 (Sr = 1.4) due to evolution of the Ni valence from Ni 2+ to Ni 3+ compared with LNO 214 . They found significantly larger variations of cell parameters a and c above 600 °C.…”
Section: Control Of Oxygen Stability In Rp Oxidesmentioning
confidence: 99%
“…An acceptor-type strontium doping of La 2 NiO 4 was extensively studied earlier [4][5][6]. The addition of strontium increases total conductivity of the oxides, although it significantly diminishes oxygen content [5].…”
Section: Introductionmentioning
confidence: 99%
“…An acceptor-type strontium doping of La 2 NiO 4 was extensively studied earlier [4][5][6]. The addition of strontium increases total conductivity of the oxides, although it significantly diminishes oxygen content [5]. The thermal expansion coefficient (TEC) of La 2− Sr NiO 4 in the 0<x<0.6 range is almost constant and equals to and La 2− Sr NiO 4 by iron exhibits an opposite effect: gradual decrease of electric conductivity along with the rise of interstitial oxygen concentration [7].…”
Section: Introductionmentioning
confidence: 99%